Legal Provisions with Basic Principles in Labor Enforcement: Analysis of Effectiveness and Challenges - Ririn Sofiana; Uzlifatul Maulidiyah; Ilmi Mufidah; Aisyatul Hasanah; Diah Putri Rusadi (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
Labor enforcement is an important process in ensuring the protection of workers' rights, ensuring fairness in industrial relations, and promoting worker welfare. This article presents a basic overview of labor enforcement by identifying the main principles, related regulations, and mechanisms used to carry out such enforcement. Through analytical descriptive research, we conclude that labor enforcement plays a crucial role in building a fair and safe work environment for workers in various sectors and job levels. With the existence of principles as a defense of workers' rights regarding work contracts, wages, health standards and union protection. The aim is to guarantee equal protection for all workers and the fulfillment of their rights, these principles must be applied firmly and consistently. The effectiveness is carried out in three stages, namely in the form of educational preventive, non-judicial repressive, and judicial repressive. If there is a dispute over rights or interests, the effort that can be taken is in the form of negotiations. There are also sanctions for company violations of industrial relations rights in the form of administrative, criminal and civil sanctions.